Incidence of injuries and their prevention in Czech ice hockey players - Carboch, J.; Praveckovßa, P.; Štefka, M. (The Journal of Sports Medicine and Physical Fitness, 2025)
BACKGROUND: Ice hockey is a dynamic game. We can observe collisions between the players that bring a risk of injury. There are many hockey clubs in the Czech Republic. These clubs raise great hockey players and many competing players in various levels of national leagues. The aim of this study was to map injuries in Czech hockey players and outline the situation of injury prevention and body care in ice hockey players.